(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed 1) to study and analyze the condition of the problems and effects on religious and cultural tourism of the southeast region for economic cooperation in the ASEAN community, 2) to present the strategy of on religious and cultural tourism of the southeast region for economic cooperation in ASEAN community. This research is qualitative. The documentary studies and field studies were used. Finally, to present the findings with a method of descriptive analysis. The results indicated that 1) the condition of the problems and effects on religious and cultural tourism of the southeast region for economic cooperation in ASEAN community found that nowadays, places for travel religiously and culturally, there are problems in the sector that people do not truly understand the intentions of their originators. These places had a deficiency of creating the hallmarks in religious sites, the staff at religious and cultural attractions are inadequate to facilitate and provide relevant knowledge, as well as lack of clear tourism management. Tourist context local authorities also non-existence integrated work. 2) the strategy of on religious and cultural tourism of the southeast region for economic co-operation in the ASEAN community found that public relations invite local personnel to participate in activities to disseminate and convey experiences. The knowledge of the religious site is organized with outstanding activities and information. It should have tourism programs; signs in each location and should be written in the ASEAN languages. Prominently, the website of each location should be provided for easy searching.